Analytical study of different sample of Kithul Jaggery (prepared by using Caryota Urens) - Buwanekabahu, I.P.; Herapathdeniya, S.K.M.K. (Faculty of Indigenous Medicine, University of Colombo; Ministry of Health, Sri Lanka, 2023)
Kithul Jaggery a unique unrefined sugar derived from the sap of the Kithul palm (Caryota Urens) in Sri Lanka. It is widely distributed palm in Asia, which is recognized for its smooth cylindrical trunk, large crown-like leaves and ...
Keywords: Kithul palm; Kithul sap; Kithul jaggery; Organoleptic; Physicochemical